Electrical studies and plasma characterization of an atmospheric pressure plasma jet operated at low frequency - Giuliani, Leandro Estanislao (2013)
Low-temperature, high-pressure plasma jets have an extensive use in medical and biological applications. Much work has been devoted to study these applications while comparatively fewer studies appear to be directed to the discharge itself. In this work, in order to better understand the kind of electrical discharge and the plasma states existing in those devices, a study of the electrical characteristics of a typical plasma jet, operated at atmospheric pressure, using either air or argon, is reported. It is found that the experimentally determined electrical characteristics are consistent with the model of a thermal arc discharge, with a highly collisional cathode sheet. The only exception is the case of argon at the smallest electrode separation studied, around 1 mm in which case the discharge is better modeled as either a non-thermal arc or a high-pressure glow. Also, variations of the electrical behavior at different gas flow rates are interpreted, consistently with the arc model, in terms of the development of fluid turbulence in the external jet.